Analisis Pengaruh Digital Marketing terhadap Pertumbuhan Ekonomi Masyarakat pada Usaha Penjualan Ikan Asin dalam Perspektif Syariah di Era Society 5.0 (Studi Kasus di Desa Jorong Kecamatan Jorong Kabupaten Tanah Laut) - M. Alfis Nor Abdi; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of digital technology in the Society 5.0 era has had a major impact on the marketing patterns of micro, small, and medium enterprises, including the salted fish business in Jorong Village, Tanah Laut Regency. Digital marketing has become one of the strategies that can help business actors expand market reach, increase sales, and support community economic growth. This study aims to analyze the influence of digital marketing on community economic growth in the salted fish business from a sharia perspective in the Society 5.0 era. This research uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation involving salted fish business actors in Jorong Village. The results of the study indicate that the use of social media such as WhatsApp, Facebook, Instagram, and TikTok has helped business actors increase salted fish sales and expand marketing reach to areas outside the region. In addition, the implementation of digital marketing has had a positive impact on increasing community income and creating new business opportunities in packaging and product distribution. From a sharia perspective, the digital marketing practices implemented by business actors generally apply the principles of honesty, transparency, and fairness in transactions, in accordance with Islamic economic values. Therefore, digital marketing can be an effective strategy in supporting sharia-based community economic growth in the Society 5.0 era.